Perforating arteries of the thigh: An anatomical and radiological study. Issue 2 (8th January 2016) - Dissanayake, Ravi; Spelman, Christopher; Balasubramanium, Umatheepan; McPherson, Rory; Martin, Thomas; Buckenham, Tim
Abstract: Introduction: We aimed to advance the understanding of the anatomy of the perforating branches of the profunda femoris artery to facilitate the avoidance of iatrogenic injury in surgery around the thigh and ensure safe percutaneous embolisation. Methods: Dissection was carried out on seven cadavers, examining the relationship of the point of origin of the perforating branches of profunda femoris, relative to lines connecting palpable bony landmarks (lines A and B). These were compared with 16 computed tomography angiograms (CTA). Left to right variation within subjects and variation between the dissection and imaged group was examined. The anatomy of the two groups was then compared with that described in anatomical textbooks. Results: The side to side variation in number of perforators was not significant in the dissection ( P = 0.20) nor the CT group ( P = 0.70). Similarly, the point of origin of the perforating vessels along lines A and B did not demonstrate any significant difference except for the fourth perforator along line B ( P = 0.03). There was no significant difference in points of origin along line B between the dissection and CT groups for the first four perforators on the left ( P = 0.51, P = 0.80, P = 0.66, P = 0.09 respectively) and right ( P = 0.79, P = 0.45, P = 0.56, P = 0.11 respectively). The number and distribution of perforators were then compared with commonly used anatomical texts. Conclusion: As in other parts of the body, textbook descriptions of anatomical structures may not be reflected consistently in vivo . However, the perforating branches of the profunda femoris demonstrate a predictable topographical relationship to palpable bony landmarks.